ANALISIS PERBEDAAN TINGKAT PROFITABILITAS SEBELUM DAN SESUDAH PENGUNGKAPAN CSR (CORPORATE SOCIAL RESPONSIBILITY) PADA PERUSAHAAN DALAM INDUSTRI PERTAMBANGAN DAN FARMASI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Herry, Yustina; Ariyanto, Stefanus (Bina Nusantara University, 2012)
The main purpose of the company used to gain maximum profits, now has changed with more attention to environmental and social aspects (triple bottom line) in order to create balance in the implementation. The research was conducted with the aim to analyze whether there are differences in the level of profitability as seen from the ratio of profitability, namely NPM (Net Profit Margin), ROA (Return on Assets) and ROE (Return On Equity) both before and after the disclosure of Corporate Social Responsibility. The sample used in this study is companies in the mining and pharmaceutical industries listed in the Indonesia Stock Exchange disclosing CSR in the period of 2003-2008 in the annual report or separate sustainability report. There are 10 samples taken by purposive sampling method, which meets the criteria. Data were analyzed using SPSS 16.0. Hypothesis testing is performed using paired two-sample test (paired sample t-test). The result of research indicates that there are no difference in profitability at the time before and after the disclosure of CSR.Â